Extraction of heavy-flavor transport coefficients in QCD matter - Rapp, Ralf; Braun-Munzinger, Peter; Pawlowski, Jan M. (Nuclear physics. A, Nuclear and hadronic physics, 2018)
We report on broadly based systematic investigations of the modeling components for open heavy-flavor diffusion and energy loss in strongly interactin…
Gesehen am 16.04.2019